2008
DOI: 10.1063/1.2903505
|View full text |Cite
|
Sign up to set email alerts
|

Origin of conductive surface layer in annealed ZnO

Abstract: The highly conductive surface layers found in nearly all as-grown or annealed bulk ZnO wafers are studied by temperature-dependent Hall-effect and secondary-ion mass spectroscopy (SIMS) measurements. In this work, we have used annealing in N2 at 900°C, and forming gas (5% H2 in N2) at 600°C, to cause a large enough surface conduction that SIMS measurements can be reliably employed. The increased near-surface donor density, as determined from two-layer Hall-effect modeling, is consistent with an increased near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…The N d surf term describes the sharp N d eff increase within the outer few nanometers due to H and perhaps to impurity segregation from the bulk. 19 DLTS of both Zn-and O-face diodes reveal two dominant traps, including the well-known bulk traps E 3 ͑0.27 eV͒ and E 4 ͑0.49͒. 20,21 However, a surface-related trap, E s ͑Ͻ ϳ 95 nm deep, 0.49 eV͒ for the Pd-/Zn-face SBDs, made on 1 h ROP-treated ZnO, was not observed on the SBDs in this study.…”
Section: Figmentioning
confidence: 47%
“…The N d surf term describes the sharp N d eff increase within the outer few nanometers due to H and perhaps to impurity segregation from the bulk. 19 DLTS of both Zn-and O-face diodes reveal two dominant traps, including the well-known bulk traps E 3 ͑0.27 eV͒ and E 4 ͑0.49͒. 20,21 However, a surface-related trap, E s ͑Ͻ ϳ 95 nm deep, 0.49 eV͒ for the Pd-/Zn-face SBDs, made on 1 h ROP-treated ZnO, was not observed on the SBDs in this study.…”
Section: Figmentioning
confidence: 47%
“…Surface electron accumulation layers are known to have a pronounced effect on the measured conductivity and its temperature dependence [139,140,146,147], and so such a surface contribution cannot be ignored when considering conductivity in TCOs. Recent measurements also indicate that an accumulation of electrons can also be induced at the surfaces of other, more complex, oxides such as SrTiO 3 , indicating that this phenomenon may indeed be rather general across the oxide semiconductors [148,149].…”
Section: Surface Conductivitymentioning
confidence: 99%
“…This represents the lowest surface concentration for any ZnO sample that we have ever measured. Additionally, this low value for n sh,max indicates that no significant surface segregation of group III impurities, such as Al, Ga, or In, has occurred as has been observed 15 recently in thermally annealed samples. It is interesting to note that the two-layer model fit of the PPCrelaxed sample shows an increase in the concentrations of both the 50 and 400 meV donors as well as the acceptor concentration as compared to the as-received sample ͑see Table I͒.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] Changes in the electrical conductivity by several orders of magnitude have been attributed 3,[8][9][10][11] to surface accumulation or depletion layers produced by adsorbed gases such as H or O and can be enhanced 12,13 by UV light irradiation. More recent work [14][15][16][17] has demonstrated that the origin of the surface conductive layer in ZnO is more complicated than the simple adsorption model and has focused on the development of quantitative tools to analyze the surface donors and acceptors. In this work, we investigate changes in the surface conduction of hydrothermal ZnO which are produced by light exposure in vacuum and demonstrate that irradiation with UV light can effectively and permanently remove the conductive surface layer that is observed in almost all commercial ZnO samples.…”
Section: Introductionmentioning
confidence: 99%